Identification and mode of formation of hopanoid nitriles in archaeological soils. (January 2016) - Adam, Pierre; Schaeffer, Philippe; Schmitt, Gaby; Bailly, Lucile; Courel, Blandine; Fresnais, Margaux; Fossurier, Carole; Rohmer, Michel
Graphical abstract: Highlights: Hopanoid nitriles in archaeological soils identified from synthesis. Mode of formation investigated from laboratory experiments. Experiments involved a hopanoid aldehyde or hopanoid polyol, H2 O2 and NH3 . The formation of nitriles involves oxidative steps and N incorporation. Abstract: In the course of investigation of lipid extracts from archaeological soils from two Merovingian tombs (7th Century, Ichtratzheim, France) in an agricultural area, a series of N-containing hopanoids was detected. They were postulated to correspond to C31 –C33 hopanoid nitriles on the basis of mass spectrometry. The C32 homologue was unambiguously identified by comparison with a standard obtained by synthesis. The mode of formation of the compounds was investigated using laboratory simulation experiments involving either N -acetyl-aminobacteriohopanetriol as a model compound representative of bacterial hopanoids with polyfunctionalized side chains, or C32 hopan-32-al. The experiments led us to propose that the formation of the nitriles from C35 biohopanoid polyols could result from a two step process involving initially an oxidation step leading to the shortening of the functionalized side chain and a second step during which N is incorporated. In the context of the soils containing archaeological wood remains from tombs and found in an agricultural area, oxidants would certainly be available, notably in the form of O2 diffusing from the surface or H2 O2 produced during wood degradation by wood-rotting fungi. Possible N sources could be residual N from the decomposing body within the tomb or manure and fertilizers used for field amendment. The laboratory experiments also gave a better insight into the diagenetic processes leading to the side chain shortening of the hopanoids. In particular, it could be shown that C31 hopanoids also derive from tetrafunctionalized hopanoids upon diagenesis and not solely from pentafunctionalized hopanoids as generally suggested in the literature.